Business Models and Stock Exchange Performance - Empirical Evidence - Baris Serifsoy (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2005)
In recent years stock exchanges have been increasingly diversifying their operations into related business areas such as derivatives trading, post-trading services and software sales. This trend can be observed most notably among profit-oriented trading venues. While the pursuit for diversification is likely to be driven by the attractiveness of these investment opportunities, it is yet an open question whether certain integration activities are also efficient, both from a social welfare and from the exchanges' perspective. Academic contributions so far analyzed different business models primarily from the social welfare perspective, whereas there is only little literature considering their impact on the exchange itself. By employing a panel data set of 28 stock exchanges for the years 1999-2003 we seek to shed light on this topic by comparing the factor productivity of exchanges with different business models. Our findings suggest three conclusions: (1) Integration activity comes at the cost of increased operational complexity which in some cases outweigh the potential synergies between related activities and therefore leads to technical inefficiencies and lower productivity growth. (2) We find no evidence that vertical integration is more efficient and productive than other business models. This finding could contribute to the ongoing discussion about the merits of vertical integration from a social welfare perspective. (3) The existence of a strong in-house IT-competence seems to be beneficial to overcome lower productivity growth associated with complex business models.
Keywords: C61; C24; F39; C23; G32; 330; exchanges; demutualization; post-trading; derivatives; software; DEA; Malmquist-Productivity; bootstrapping; Wertpapierbörse; Diversifikation; Geschäftsmodell; Wirtschaftliche Effizienz; Schätzung; Welt